PERAN STRATEGIS PENDIDIKAN ISLAM DALAM MEMAJUKAN PEMBANGUNAN NASIONAL: (The Strategic Role of Islamic Education in Advancing National Development) - Ine Ratu Fadliah (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2025)
Islamic education holds a strategic significance in shaping character, morality, and the quality of human resources with high competitiveness, thereby contributing directly to national development. In the context of globalization and dynamic societal change, Islamic education in Indonesia not only faces the challenges of modernization but also plays a crucial role in preserving Islamic values and local cultural wisdom. This study aims to examine the existence and contribution of Islamic education to national progress from historical, institutional, and functional perspectives. A descriptive qualitative approach was employed in this study, utilizing content analysis on various secondary sources such as scholarly journals, policy documents, and previous research findings. Thematic analysis was conducted using the Miles and Huberman framework to identify patterns of Islamic education’s contribution to the economic, social, and cultural development of the nation. The findings reveal that Islamic education, through institutions such as pesantren and madrasah, has transformed into a social change agent that adapts to contemporary developments. This form of education not only instills spiritual and ethical values but also fosters critical thinking, leadership, and innovation skills necessary for building a globally competitive nation. Furthermore, the integration of Islamic values with the principles of sustainable development and character education positions Islamic education as a strategic foundation for balanced national progress, encompassing both material and spiritual dimensions. Strengthening the Islamic education system is a vital investment in realizing the vision of a progressive, ethical, and resilient Indonesia in the face of global challenges.